Transcultural Adaptation and Psychometric Properties of Portuguese Version of the Spiritual Needs Questionnaire (SpNQ) Among HIV Positive Patients in Brazil - Valente, Tânia Cristina de Oliveira (Religions, 2018)
The Spiritual Needs Questionnaire (SpNQ), originally written in the German language, was translated and validated into 11 languages, but not Latin languages, such as Brazilian Portuguese. This study aimed to determine the psychometric properties of the SpNQ after translation and transcultural adaptation to the Portuguese language, identifying unmet spiritual needs in a sample of patients living with HIV in Brazil. This pioneering study conformed a four-factor structure of 20 items, differentiating Religious Needs (a = 0.887), Giving/Generativity Needs (a = 0.848), Inner Peace (a = 0.813) and a new item: Family Support Needs (a = 0.778). The Brazilian version of the SpNQ (SpNQ-BR) had good internal validity criteria and can be used for research of the spiritual needs for Brazilian patients. The cross-cultural adaptation and comparison with previous studies showed that the SpNQ is sensitive to the cultural characteristics of different countries.